Pengembangan Aplikasi Perangkat Bergerak Berbasis Lokasi Untuk Perencanaan Perjalanan Wisata Blitar Berdasarkan Rute Terpendek - Abidin Adi Prasetyo; Agi Putra Kharisma; Issa Arwani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
The increasing number of tourist arrivals in Blitar City each year has an impact on the increasing points of tourist sites in Blitar. The fact that there are many tourist attractions in the Blitar region close to the location makes the tendency of tourists to visit several tourist attractions in one travel route . Tourists certainly want the optimal route with the shortest distance for their tour so that they can save time and fuel costs of their vehicles. The problem in determining the route with the shortest distance is that there are many path options that exist between locations because in reality from place A to place B only not only has one pathway. With these problems researchers developed the Location Based Mobile Device Application for Blitar Travel Planning Based on the Shortest Route by using the Traveling Salesman Problem approach to solve this problem. In the design phase it uses the prototyping method so that if there are changes to the design iterations can be carried out for the revision or improvement process. At this stage of testing, it uses validation testing on functional and non-functional requirements and reusability testing using the System Usability Scale Questionnaire. Based on the test results on the development of applications that are valid on functional and non-functional requirements and can be run on several Android devices.